DOMINASI LAKI-LAKI TERHADAP PEREMPUAN BUGIS - Zainal Zainal (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2016)
This paper seeks to find the logic of marginalization of women in Bugis culture by shifting the orientation of the feminist movement which sees a great tendency to confront the "head to head" between men and women as two hostile poles separate from their cultural context. The focus is on the cultural context that conditioning men and women so that they split into two hostile poles. At this point the problem lies in a patriarchal system that engages with the logic of market capitalism. The method used is ethnographic research to trace the hidden codes and marginalization logic that occur behind events. The ethnographic data are interpreted critically to find a through description of the domination of men who marginalized women in Bugis culture. Thus, the purpose of research is to find the root of the problem in the form of hidden systems and structures that form the basis of cultural practice. The data were taken in the form of snippets case which then interpreted to be focus of important points. In Bugis culture there are three important points on how the patriarchal system with the allies of market capitalism show the conditioning of inequality, in which women and men as young people experience systemic symbolic violence. First point: Family domain. Second Point: Cash in the Bugis marriage ritual process, third point: Language context, discourse (daily conversation) and hidden code in Bugis culture. Finally it is found that the root of the problem of gender inequality lies in the system and structure of Bugis culture, in which the categories of sex and gender, social class, social institutions and the social character of men and women as an inseparable of the unity.